Modal behaviour of vertical axis wind turbine comprising prestressed rotor blades: a finite element analysis - Asr, Mahdi Torabi; Masoumi, M. M.; Mustapha, Faizal (Universiti Putra Malaysia Press, 2017)
Pre-stressing is a concept used in many engineering structures. In this study prestressing in the form of axial compression stress is proposed in the blade structure of H-Darrieus wind turbine. The study draws a structural comparison between reference and prestressed configurations of turbine rotor with respect to their dynamic vibrational response. Rotordynamics calculations provided by ANSYS Mechanical is used to investigate the effects of turbine rotation on the dynamic response of the system. Rotation speed ranging between 0 to 150 rad/s was examined to cover the whole operating range of commercial instances. The modal analysis ends up with first six mode shapes of both rotor configurations. As a result, the displacement of the proposed configurations reduced effectively. Apparent variations in Campbell diagrams of both cases indicate that prestressed configuration has its resonant frequencies far away from turbine operation speeds and thus remarkably higher safety factor against whirling and probable following failures.